ISOLASI MIRISTISIN DARI MINYAK PALA (Myristica fragrans) DENGAN METODE PENYULINGAN UAP - Suprihatin, S. Ketaren, S. Ngudiwaluyo dan TINA. Friyadi (Jurnal Teknologi Industri Pertanian, 2007)
ABSTRACTMyristicin (C11H12O3) is one of the most important constituents of the nutmeg oil.  Myristicin is toxic and hallucinogenic agent in nutmeg and mace.  Isolation of myristicin can be carried out by steam distillation.  The objective of this research was to extract myristicin from nutmeg oil by steam distillation. Nutmeg oil was distilled at  pressure 15 mmHg, 145, 150 and 155oC for concentration.  The highest myristicin content in oil fraction was 70.10% with concentration 786.99 g/l obtained by distillation at 145oC.  Under this operating condition the yield of oil fraction was 6.72%.  Isolation myristicin by steam distillation method was conducted at atmospheric pressure for 2, 2.5 and 3 hours.  The highest myristicin content in oil fraction was 84.44% with concentration 916.25 g/l which was obtained by steam distillation of 3 hours.Key words : Myristicaceae, myristicin, nutmeg oil, steam distillation